2008
DOI: 10.1021/cg701112x
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of ZnO Powders from Aqueous Solutions with Water-Soluble Polymers

Abstract: ZnO powders were synthesized in the presence of water-soluble polymers. These polymers have effects on the nucleation and growth of ZnO crystals in solution, resulting in difference in crystalline morphologies. The role of polymers is 2-fold: first, indiscriminating adsorption of Zn(II) ions onto the polymer surfaces, which leads to the site-specific supersaturation with respect to the nucleation of ZnO, and secondarily, morphological development by interactions of zinc species with polymers and their hydrolyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus, we feel that it is important to investigate the aqueous phase synthesis of ZnO nanostructures of various shapes using the biodegradable “green” ascorbic acid molecule as a capping agent. A detailed survey of the literature shows that compared to other-shaped ZnO nanostructures there exist only a few reports on the preparation of hierarchical ZnO nanostructures that are somewhat flowerlike in appearance by wet-chemical methods. , For example, Zhang et al have reported the preparation of ZnO nanostructures of flower-, rod-, and prism-shaped morphology by decomposing the zinc precursors at higher temperature . Liu et al have synthesized ZnO nanoflowers by the alkaline hydrolysis of zinc nitrate using ammonium hydroxide. , An array of multineedle-shaped ZnO nanostructures, whose individual particle morphology is closer to that of a flower, have also been prepared by Masuda et al using site-selective deposition techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we feel that it is important to investigate the aqueous phase synthesis of ZnO nanostructures of various shapes using the biodegradable “green” ascorbic acid molecule as a capping agent. A detailed survey of the literature shows that compared to other-shaped ZnO nanostructures there exist only a few reports on the preparation of hierarchical ZnO nanostructures that are somewhat flowerlike in appearance by wet-chemical methods. , For example, Zhang et al have reported the preparation of ZnO nanostructures of flower-, rod-, and prism-shaped morphology by decomposing the zinc precursors at higher temperature . Liu et al have synthesized ZnO nanoflowers by the alkaline hydrolysis of zinc nitrate using ammonium hydroxide. , An array of multineedle-shaped ZnO nanostructures, whose individual particle morphology is closer to that of a flower, have also been prepared by Masuda et al using site-selective deposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed survey of the literature shows that compared to othershaped ZnO nanostructures there exist only a few reports on the preparation of hierarchical ZnO nanostructures that are somewhat flowerlike in appearance by wet-chemical methods. 38,[42][43][44][45][46][47][48][49][50][51] For example, Zhang et al have reported the preparation of ZnO nanostructures of flower-, rod-, and prism-shaped morphology by decomposing the zinc precursors at higher temperature. 22 Liu et al have synthesized ZnO nanoflowers by the alkaline hydrolysis of zinc nitrate using ammonium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…In CS series nanobres, many grains have hard edges compared with those of the respective CP series nano-bres. This can be due to the presence of SAN at the nucleation and growth temperature of Co 3 O 4 grains to guide the growth in certain direction, 24 which happens at $327 C. In CP series nanobres, the degradation of PEtOx takes place straight away aer the formation of Co 3 O 4 nucleates from CATH, where as in the case of SAN, it is assumed that the degradation starts as the nucleation progresses; therefore, the polymer may be available for the controlled growth of the crystals. A mechanism of The SEM-EDS results of the Co 3 O 4 nanobres obtained from the two types of composite bres are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%